2011
DOI: 10.1073/pnas.1110428108
|View full text |Cite
|
Sign up to set email alerts
|

Mst1 and Mst2 protein kinases restrain intestinal stem cell proliferation and colonic tumorigenesis by inhibition of Yes-associated protein (Yap) overabundance

Abstract: Ablation of the kinases Mst1 and Mst2, orthologs of the Drosophila antiproliferative kinase Hippo, from mouse intestinal epithelium caused marked expansion of an undifferentiated stem cell compartment and loss of secretory cells throughout the small and large intestine. Although median survival of mice lacking intestinal Mst1/ Mst2 is 13 wk, adenomas of the distal colon are common by this age. Diminished phosphorylation, enhanced abundance, and nuclear localization of the transcriptional coactivator Yes-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
469
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(494 citation statements)
references
References 47 publications
19
469
3
3
Order By: Relevance
“…It is also possible that basal Myc activity plays a minor role in normal homeostasis of mammalian intestines, but its elevated activity is essential for abnormal proliferation due to oncogenic mutations or loss of APC. In this regard, Myc may resemble Yap, which appears to be dispensable for normal homeostasis of the intestine but is required for overproliferation of intestine cells induced by injury or oncogenic mutations [39,40]. It would be interesting to determine whether Myc is also regulated by Hpo signaling and plays a role in adult tissue regeneration in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that basal Myc activity plays a minor role in normal homeostasis of mammalian intestines, but its elevated activity is essential for abnormal proliferation due to oncogenic mutations or loss of APC. In this regard, Myc may resemble Yap, which appears to be dispensable for normal homeostasis of the intestine but is required for overproliferation of intestine cells induced by injury or oncogenic mutations [39,40]. It would be interesting to determine whether Myc is also regulated by Hpo signaling and plays a role in adult tissue regeneration in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Later evidence supports that in many tissues the Hippo pathway has a stronger impact on the tissue-specific stem cell compartment, possibly inhibiting their proliferation or self-renewal. It was first observed that intestinal-specific overexpression of YAP or knockout of Mst1/2 in mice caused marked expansion of the stem cell compartment (Camargo et al, 2007;Zhou et al, 2011a). Knockout of Hippo pathway components Mst1/2, Sav1, and Mer in liver also leads to accumulation of liver stem cells (Benhamouche et al, 2010;Lee et al, 2010;Lu et al, 2010;Song et al, 2010).…”
Section: The Hippo Pathway Limits the Pool Of Tissue-specific Progenimentioning
confidence: 99%
“…In the mouse, YAP overexpression or conditional deletion of Mst1/2 leads to hepatomegaly (14 -16). Removal of Mst kinases in the mouse gastrointestinal tract leads to increased numbers of stem cells and proliferative transit amplifying cells and an impairment of epithelial cell differentiation (17). Moreover, the Hippo pathway is critical for establishment and maintenance of the intestinal crypt microenvironment and it is required for repair of the intestinal epithelium following injury (14,17,18).…”
mentioning
confidence: 99%
“…Deregulation of Hippo/YAP signaling has been implicated in intestinal tumorigenesis (14,17,18). YAP expression is elevated in human primary colonic tumors compared with its expression in uninvolved tissue and YAP expression is increased in the intestinal tumors that arise in the adenomatous polyposis coli multiple intestinal neoplasia (APC min ) mouse (14,18,19).…”
mentioning
confidence: 99%